2004
DOI: 10.1023/b:jach.0000009936.82613.ad
|View full text |Cite
|
Sign up to set email alerts
|

Study of a high power density sodium polysulfide/bromine energy storage cell

Abstract: Nickel catalyst supported on carbon was made by reduction of nickelous nitrate with hydrogen at high temperature. Ni/C catalyst characterization was carried out by XRD. It was found that the crystal phase of NiS and NiS 2 appeared in the impregnated catalyst. Ni/C and Pt/C catalysts gave high performance as the positive and negative electrodes of a sodium polysulfide/bromine energy storage cell, respectively. The overpotentials of the positive and negative electrodes were investigated. The effect of the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…The ZneCe redox flow battery is a system that combines the very negative zinc couple with a very positive cerium couple to yield an open-circuit voltage that is higher than any of its commercial competitors [40]. It has been under development since the early 1990s by Electrochemical Design Associates Inc [41].…”
Section: Zinc/cerium Redox Flow Cellsmentioning
confidence: 99%
“…The ZneCe redox flow battery is a system that combines the very negative zinc couple with a very positive cerium couple to yield an open-circuit voltage that is higher than any of its commercial competitors [40]. It has been under development since the early 1990s by Electrochemical Design Associates Inc [41].…”
Section: Zinc/cerium Redox Flow Cellsmentioning
confidence: 99%
“…Different kinds of RFBs have been studied at our research group since 1989 [3,[17][18][19][20][21][22][23][24][25][26]. In this work, we focused on the characteristics and performance of the VRB cell stack recently developed in our lab.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the polarization of the milled WS 2 is not influenced by mass transport. Table III summarizes the Tafel parameters evaluated from the potentiostatic steady state polarization data shown in Figure 14, fitted to the exponential approximation of the Butler-Volmer equation: 79 i SS = i 0 10 ±η/b [7] where i SS is the steady state current, i 0 is the exchange current density. b is the Tafel slope, and η is the overpotential.…”
Section: Resultsmentioning
confidence: 99%
“…The linearity of the simulated kinetic polarization plots of Figure 20 indicate that a single kinetic regime prevails for polysulfide reduction and a single kinetic regime prevails for polysulfide oxidation Mass transport and anodic passivation.-Several authors have observed the 'passivation' of their electrodes during polysulfide oxidation due to the formation of a S film. [7][8][9]29,[107][108][109] Zhou et al propose that efficient mass transport can prevent this anodic passivation. 9 Presumably, mass transport alleviates the passivation as a result of the autocatalytic effect that polysulfides seem to exhibit upon the dissolution of the S layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation